Effect of temperature and type of ash on the amount of impurities in lime - (:unkn) unknown (BAUVERLAG BV GMBH, 2008)
In lime production, the impurities caused by fuel can be expressed by the addition of three components; CaSO4 formed by oxidation of sulfur, ash and impurities caused by the reaction between ash and CaO. They increase in the function of a quadratic equation depending on the temperature. It was found that the amount of reaction-induced impurities is not related to the SiO2 concentration in the ash. Despite this, the percentage of lower melting salts contained in the ash increases the lime reactions and hence the impurity in the lime caused by the fuel.